Preventable suicides involving medicines: a systematic case series of coroners' reports in england and wales. - Anthony, G; Aronson, J; Brittain, R; Heneghan, C; Richards, GC (Elsevier, 2024)
Background: In England and Wales coroners have a duty to write a report, called a Prevention of Future Deaths report or PFD, when they believe that actions should be taken to prevent future deaths. Coroners send PFDs to individuals and organisations who are required to respond within 56 days. Despite the increase in mental health concerns and growing use of medicines, deaths reported by coroners that have involved medicine-related suicides had not yet been explored. Therefore, this study aimed to systematically assess coroners’ PFD reports involving suicides in which a medicine caused or contributed to the death to identify lessons for suicide prevention. Methods: Using the Preventable Deaths Tracker database https://preventabledeathstracker.net/), 3037 coroners’ PFD reports in England and Wales were screened for eligibility between July 2013 and December 2019. Reports were included if they involved suicide or intentional self-harm and prescribed or over-the-counter medication; illicit drugs were excluded. Following data extraction, descriptive statistics, document and content analysis were performed to assess coroners’ concerns and the recipients of reports. Results: There were 734 suicide-related coroner reports, with 100 (14%) reporting a medicine. Opioids (40%) were the most common class involved, followed by antidepressants (30%). There was wide geographical variation in the writing of reports; coroners in Manchester wrote the most (18%). Coroners expressed 237 concerns; the most common were procedural inadequacies (14%, n = 32), inadequate documentation and communication (10%, n = 22), and inappropriate prescription access (9%, n = 21). 203 recipients received the PFDs, with most sent to NHS trusts (31%), clinical commissioning groups (10%), and general practices (10%), of which only 58% responded to the coroner. Conclusions: One in four coroner reports in England and Wales involved suicides, with one in seven suiciderelated deaths involving a medicine. Concerns raised by coroners highlighted gaps in care that require action from the Government, health services, and prescribers to aid suicide prevention. Coroner reports should be routinely used and monitored to inform public health policy, disseminated nationally, and responses to coroners should be transparently enforced so that actions are taken to prevent future suicides.